Cost benefit analysis and energy savings of using compression and absorption chillers for air conditioners in hot and humid climates - Shekarchian, M.; Moghavvemi, M.; Motasemi, F.; Mahlia, T.M.I. (2012)
The electricity consumption growth has increased steadily in the recent decade which is a great concern for the environment. Increasing the number of high-rise air-conditioned buildings and the rapid use of electrical appliances in residential and commercial sectors are two important factors for high electricity consumption. This paper investigates the annual energy required for cooling per unit area and the total energy cost per unit area for each type of air conditioning systems in hot and humid climates. The effects of changing the coefficient of performance (COP) of absorption chillers on cost saving was also investigated in this study. The results showed that using absorption chillers for cooling will increase the amount of energy consumption per unit area; however the energy cost per unit area will decrease. In addition this research indicates that for each 0.1 increment in COP of absorption chillers, there is about 500 USD/m2 saved cost.